2009
DOI: 10.1021/jp905134b
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene: A Key Growth Precursor for Single-Walled Carbon Nanotube Forests

Abstract: The growth of tall, single-walled carbon nanotube (SWNT) forests is often believed to require the use of specific feedstocks (e.g., ethanol) or etchants (e.g., water). Here, on the basis of mass spectrometry for hydrogendiluted methane in a microwave plasma-enhanced chemical vapor deposition (PECVD) reactor, we develop a purely thermal CVD process for SWNT forests without an etchant gas. The thermally grown SWNT forests are found to have a similar high quality, purity, growth rate, areal density, diameter, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 39 publications
0
110
2
Order By: Relevance
“…Moreover C 2 H 2 and C 2 H 4 decompose more easily at the catalyst surface than CH 4 at lower temperature [41]. Furthermore, C 2 H 2 [42]and C 2 H 4 [43] have been reported as key precursors for the efficient growth of SWCNTs by CVD. Bell et al [8] also confirmed that C 2 H 2 was the dominant precursor for CNT formation in a C 2 H 2 /NH 3 plasma.…”
Section: Effect Of Gas Mixture Ratiosmentioning
confidence: 99%
“…Moreover C 2 H 2 and C 2 H 4 decompose more easily at the catalyst surface than CH 4 at lower temperature [41]. Furthermore, C 2 H 2 [42]and C 2 H 4 [43] have been reported as key precursors for the efficient growth of SWCNTs by CVD. Bell et al [8] also confirmed that C 2 H 2 was the dominant precursor for CNT formation in a C 2 H 2 /NH 3 plasma.…”
Section: Effect Of Gas Mixture Ratiosmentioning
confidence: 99%
“…For example, plasma can be used to make HCCH from coal, 1 natural gas, 2 and methane. 3,4 Conversely acetylene plasmas are used for a variety of chemistries; 5 they are used to make C 2 , 6 CH*, 7 fullerenes, 8 diamonds, 9 carbon nanoparticles, 10 hydrocarbon nanoparticles, 11 nanotubes, 12,13 and polymers, 14 as well as other chemical processes. 15,16 Acetylene plasmas are used to provide a variety of different coatings.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that they are instrumental in the formation process of carbon nanomaterials. Several previous investigations showed that LHCs generated in this work (benzene 21,22 , ethylene 23,24 , methane 18 , and acetylene 20 ) can be used as carbon feedstock in the production of nanomaterials. For example, when polyethylene was used as carbon feedstock for CNM SEM images show entangled nanomaterials which cover (not uniformly) the catalyst mesh under all conditions.…”
Section: Microstructural Analysis Of Catalyzed Materialsmentioning
confidence: 89%
“…For TEM samples, the meshes were sonicated in a 100% ethanol solution and the products and without the catalyst system (the values are listed in parts per million -ppm). Several prior works have shown that the hydrocarbons can be used as important carbon donors in the production of CNMs using the catalytic CVD method [18][19][20][21][22][23][24] . The CCVD process used in this work basically consisted of thermal dehydrogenation reactions whereby a transition metal catalyst was used to "crack" the hydrocarbon gases into carbon and hydrogen 12 .…”
Section: Sample Characterizationmentioning
confidence: 99%